Experimental laboratory study on the acoustic response of sandstones during injection of supercritical CO2 on CRC2 sample from Otway basin Australia - Lebedev, Maxim; Mikhaltsevitch, Vassili; Bilenko, Olga; Dance, T.; Pervukhina, M.; Gurevich, Boris (Elsevier BV, 2013)
Quantitative knowledge of the acoustic response of rock from an injection site on supercritical CO2 saturation is crucial for understanding the feasibility of time-lapse seismic monitoring of CO2 plume migration. A suite of shaley sandstones from the CRC-2 well, Otway Basin, Australia is tested to reveal the effects of supercritical CO2 injection on acoustic responses. The sandstone samples were cut in different directions with respect to a formation bedding plane and varied in porosities between 14% and 29% and permeabilities between 0.2 mD and 10,000 mD. Pore pressures and temperatures were varied from 4 MPa to 10 MPa, and 23°C to 45°C respectively to cover both vapour and supercritical regions of CO2 phase diagram. CO2 is first injected into dry samples, flushed out with brine and then injected again into brine saturated samples. Such experimental protocol allows us to obtain acoustic velocities of the samples for the wide range of CO2 saturations from 0 to 100%. On injection of supercritical CO2 (scCO2) into brine-saturated samples, they exhibit observable perturbation of ~7% of compressional velocities with the increase of CO2 saturation form 0% to maximum (~50%). Changes of the dry samples before and after the CO2 injection (if any) are not traceable by acoustic methods. An applicability of implementation of fluid substitution using Gassman theory for CRC2 well has been proved in the experiments. CO2 Residual saturation of about 50% was measured by monitoring of the volume of brine displaced from the sample and was independently confirmed by computer tomography (CT) imaging of the sample before and after experiments.